2022
DOI: 10.1038/s42004-022-00793-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced thermal expansion by surface-mounted nanoparticles in a pillared-layered metal-organic framework

Abstract: Control of thermal expansion (TE) is important to improve material longevity in applications with repeated temperature changes or fluctuations. The TE behavior of metal-organic frameworks (MOFs) is increasingly well understood, while the impact of surface-mounted nanoparticles (NPs) on the TE properties of MOFs remains unexplored despite large promises of NP@MOF composites in catalysis and adsorbate diffusion control. Here we study the influence of surface-mounted platinum nanoparticles on the TE properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…It has been found that linker rotation can influence conversion and selectivity for Pt@ZIF-8 materials used in catalysis; 43 however, to the best of our knowledge the inverse question of how flexibility in MOFs is affected by NPs has not been investigated outside of a recent study from us where we focused on the thermal expansion properties of Pt@MOF composites. 44 The research areas of NP loaded MOF materials and switchable, flexible MOFs are yet not interlinked while scenarios in which network switching regulates catalysis conditions at the NPs, and in which NPs direct framework switching behavior can easily be envisioned. Therefore, we see great potential in forming this link.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that linker rotation can influence conversion and selectivity for Pt@ZIF-8 materials used in catalysis; 43 however, to the best of our knowledge the inverse question of how flexibility in MOFs is affected by NPs has not been investigated outside of a recent study from us where we focused on the thermal expansion properties of Pt@MOF composites. 44 The research areas of NP loaded MOF materials and switchable, flexible MOFs are yet not interlinked while scenarios in which network switching regulates catalysis conditions at the NPs, and in which NPs direct framework switching behavior can easily be envisioned. Therefore, we see great potential in forming this link.…”
Section: Introductionmentioning
confidence: 99%